PERAN & FUNGSI DOSEN PENASEHAT AKADEMIK - Mulyadi, Dr. (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2008)
STAIN Malang as one of institute of higher education does not stop to race in realizing its mission and vision in order to reach target of National education. Hence from that STAIN chooses certain lecturer as Counselor academic to give tuition, motivate and the advice to student academically, furthermore, in certain boundary, students really need academic adviser to support their learning process and in developing their potency. Pursuant to the background, problem and purpose of this research is to know the function and the role academic adviser in STAIN Malang.Population in this research is all students of STAIN Malang in first semester of academic year 2002-2003 amounts to 4641 students. The sample is 10% from population by random sampling technique. The method using in collecting data is questioner as prior method, beside that, documentation method and interview as support method. To test validity and reliability of measuring instrument used computer with SPS program of Sutrisno Hadi and Yuni Pamardiningsih, Gadjah Mada University, Yogyakarta. Version: IBM/IM, Copy Right Â© 2002. To analyze data use technique percentage.Academic advisers in STAIN Malang have conducted his function and role as student motivator and counselor well but not optimal yet.Keywords: role, function, and academic adviser.